PREDICTING THE RISK OF ATRIAL FIBRILLATION AND CORONARY HEART DISEASE DEVELOPMENT WITH MUTATION OF HEMOSTASIS SYSTEM GENES - D. I. Panchenko; A. S. Adamchik (Кубанский научный медицинский вестник)
Aim. This study was conducted to assess the risk of atrial fibrillation and coronary heart disease development with mutation of hemostasis system genes.Materials and methods. Genes polymorphisms of factor GII210A II (FII), G169A factor V (FV), Arg 353G1p factor VII (FVII), C677T MTHFR, 22Met (66a-g) MTRR, 675 5G / 4G PAI type 1 and 455G-A fibrinogen β (FGB) were examined in the patients of the main group and control group. The genotyping was carried out by PCR method using competing TagMan probes complementary to the polymorphic region of DNA.Results. As a result of the research, there was identified a reliable prognostic risk of the development of coronary heart disease (CHD) and atrial fibrillation paroxysms (AFP) in patients with mutations of the VII blood coagulation factor genes, mutations in the MTHFR gene, mutations in the MTRR gene.Conclusion. The obtained results indicate the risk of CHD and AFP development in patients with mutations of the VII gene of the clotting factor, mutation in the MTHFR gene and mutation in the MTRR gene. It may be the basis for early diagnosis, monitoring and treatment of this category of patients.